Recurrent Misunderstandings Eroding the Field of Communication Studies - Cibangu, Sylvain (Advances in Social Sciences Research Journal, 2025)
More than recognized, misunderstandings are a constant concomitant of human activities in industry and academia. This truism traces back to ancient writers, and communication studies is no exception. (Re)assessment of misunderstandings has the potential to refurbish skills and awareness needed to accomplish better, keener research. However, as literatures and fragmentations of communication studies build up, discussions on and/or critical accounts of ensuing misunderstandings tend to lag behind. One reason behind this shortage is a popular aversion for theory or verbiage. Another reason resides in the hype for new media and uptake thereof. Still another reason centers around the attractive dominance of big data or large-scale quantitative research. The present paper unbundled deep-seated and taken-for-granted misunderstandings crippling communication research. To this effect, the paper proposed paths forward with a refocus/rethink of central concepts, models, and definitions underpinning communication research.